EVALUATION OF A DIDACTIC MODEL USING A CONCEPTUAL APPROACH: AN INNOVATIVE TOOL APPLIED TO ECOLOGY TEACHING - Natalia A. Grigorash (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article presents various pedagogical theories offered by different researchers, theories that have been applied to the field of environmental education. On the basis of these theories a new theoretical field has been developed that helped create and test an innovative didactical instrument allowing to make it possible for students to acquire unknown for them ecological concepts. Obtained results have been demonstrated by four principles: conceptual approach, operational model, situation-problems, integration of the social side of knowledge construction. Seven phases of continual education: research of a particular ecosystem, analysis of concept characteristics, correction of the initial situation problem, debate, application of the newly acquired knowledge in different situations. An analysis of the students ability to use received information in varying contexts has been done. The underlying principles of theories presented have been explained.